Penelitian Pengolahan Air Limbah Industri Berkonsentrasi COD Tinggi Secara Anerobik dan Aerobik - Eva Dasmita (Balai Besar Kimia dan Kemasan, 1999)
One of the famous traditional food of Indonesia is tempe. Tempe is mainly produced in small scale industries. The wastewater from tempe industries contains a high organic pollutant especially from the boiling bean wastewater with COD chromium content 30, 000 mg/l -60, 000 mg/l and usually the effluent is directly blown down to the river without any treatment. To remove the high organic pollutant in industrial wastewater generally should be treated by the anaerobic and aerobic process to dare to the low cost, while the methane gas produced can be used as a fuel to boil or cook the tempe. The simple purification system of wastewater treatment with anaerobic UASB type followed with aerobic process has successfully, remove the total rate of COD content more than 90 % in anaerobic and 85 % in aerobic.